2019
DOI: 10.3389/fmicb.2019.00865
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecotoxicology of Marine Plastic Debris: A Review on Colonization and Biodegradation by the “Plastisphere”

Abstract: Over the last decades, it has become clear that plastic pollution presents a global societal and environmental challenge given its increasing presence in the oceans. A growing literature has focused on the microbial life growing on the surfaces of these pollutants called the “plastisphere,” but the general concepts of microbial ecotoxicology have only rarely been integrated. Microbial ecotoxicology deals with (i) the impact of pollutants on microbial communities and inversely (ii) how much microbes can influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
212
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(224 citation statements)
references
References 135 publications
(148 reference statements)
6
212
1
5
Order By: Relevance
“…Using light microscopy, however, Eich et al () found certain diatom taxa to specifically colonize HDPE or a biopolymer‐polyethylene terephthalate (PETE) (biodegradable) in the Mediterranean Sea. These observations support the complex interplay of the factors involved in shaping plastisphere communities (reviewed by Jacquin et al ), and the importance of understanding the colonization of new plastics in the environment over time.…”
supporting
confidence: 78%
“…Using light microscopy, however, Eich et al () found certain diatom taxa to specifically colonize HDPE or a biopolymer‐polyethylene terephthalate (PETE) (biodegradable) in the Mediterranean Sea. These observations support the complex interplay of the factors involved in shaping plastisphere communities (reviewed by Jacquin et al ), and the importance of understanding the colonization of new plastics in the environment over time.…”
supporting
confidence: 78%
“…According to a recent review by Jacquin et al [85], plastisphere communities found in the sub-surface are dominated by photoautotrophic bacteria such as cyanobacteria with the genera Phormidium and Rivularia, while the core microbiome of the seafloor and subsurface plastisphere seems to share some taxa, such as Bacteroidetes (Flavobacteriaceae) and Proteobacteria (Rhodobacteraceae and Alcanivoraceae) [42,[86][87][88]. Plastic-attached bacteria were dominated by alphaand gamma-Proteobacteria, while seawater bacteria were dominated by alpha-Proteobacteria (mainly Pelagibacter sp.)…”
Section: Plastic Polymersmentioning
confidence: 99%
“…For obvious reasons, the biodegradation of these recalcitrant plastics are exciting discoveries that give hope for the natural bioremediation of sites contaminated with plastic waste in the environment, although plastic degradation in the ocean seems to be slow at best and the anthropogenic dissemination of new plastic pollution likely far exceeds its decay 18 . Notably, this biodegradation also offers a tremendous opportunity for waste treatment: To biotechnologically upcycle plastic waste to valuable products such as bioplastics.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%